From Teacher Education to Teachers' Work: The Knowledge of Students - Delphine Tremblay-Gagnon; Cecilia Borges; Maurice Tardif (Canadian Society for Studies in Education, 2022)
In order to teach, what do teachers need to know about their students? At some point, teachers must apply the fundamental educational and developmental psychological knowledge about students learned mostly in teacher education programs, to the reality of a classroom, but what do they consider of their students in their daily practice? This research studies Quebec's teachers (Canada) point of view on what they know about students, how they know it and how they use this knowledge in their teaching. Data were collected from 25 interviews and four focus groups with teachers from elementary and high schools. The data have been analyzed through NVivo software using thematic content analysis. The analysis highlights that teachers know about their students and tend to adapt their practices, learning activities and interventions according to them and to the best of their ability. Precisely, this paper will discuss our first research question: what specific knowledge teachers possess about their students?